Luxury or normal goods? Evidence from the utilization of institutional care services for the disabled older adults in China - Xia, Xueqing; Li, Quanlun (Frontiers in public health, 2023)
Nursing care is essential for older adults with disabilities. Income plays a crucial role in determining the utilization of institutional care services. Pension benefit, as the main source of income for the older adults in China's cities and towns in their later years, is an important factor influencing the utilization of institutional care services. However, there have been no consistent findings on how pension benefits affect the utilization of institutional care services for the disabled older adults. This paper utilizes data from the 2017-2018 Chinese Longitudinal Healthy Longevity Survey. We select disabled older adults aged 65 and older, living in towns and cities, and use a probit regression model to investigate the impact of pension benefits on the utilization of institutional care services by urban disabled older adults empirically. The study shows that a 1% increase in pension benefits raises the probability that the urban disabled older adults use institutional care services by 0.03. It also finds that for low-income urban disabled older adults, the effect is statistically significantly positive at the 1% level; but for high-income urban disabled older adults, the effect is not statistically significant. The pension benefits significantly increase the probability for the disabled older adults who are male, financially dependent, and live in townships. In addition, the pension benefits significantly reduce the probability that children will provide care and pay for care services for their older parents. Institutional care service is a normal good for the urban disabled older adults, especially for low-income older adults. Therefore, higher pension benefit raises the probability of utilizing institutional care services for the urban older adults with disabilities, and this positive effect is especially pronounced for older adults who are male, financially dependent, and reside in townships. In addition, increase in the pension benefits for the disabled older adults in towns and cities reduces the burden on children by reducing the probability that children will provide care and pay for care services for the older adults.